TIME TREND AND SPATIAL DISTRIBUTION OF DENGUE IN BRAZIL - Silva, Thiago Rodrigues da; Costa, Ana Karla Araújo Nascimento; Alves, Kelle Araújo Nascimento; Santos, Alisson Neves; Cota, Matheus de França (Cogitare Enfermagem, 2022)
Objective: to determine the time trend and spatial distribution of the confirmed dengue cases in Brazil between 2009 and 2019. Method: this is an ecological and longitudinal study of a historical series of the dengue cases available in the Information System of Notifiable Health Problems. The data were analyzed by means of time trend and spatial distributions. Results: the study denoted a stationary trend of the incidence coefficient (R=0.091; p>0.05). The Midwest region stood out among the Brazilian regions, with 42.04% incidence. In relation to the Brazilian states, Acre was the one with the highest incidence: 45.06%. Finally, regarding the severe form of dengue, the Southeast region stood out with 38.35% of the cases. Conclusion: based on the epidemiological analyses, it was concluded that, in Brazil, dengue is still a relevant public health problem, given the high number of cases.